Pre Î±g-Open Functions and Pre Î±g-Closed Functions in Topology - Mookanagoudar, Sujata S (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
In this paper we introduce Â thenew class of functions namely, pre-Î±g-open functions and pre-Î±g-closed functions in topological spaces. Also, we define and study the concepts ofÂ  Î±-Î±g-open functions, (p, Î±g)-open functions, strongly-Î±g-closed functions and Î±-Î±g-closedfunctions.